2020
DOI: 10.1017/s1355617720000375
|View full text |Cite
|
Sign up to set email alerts
|

Differences in Discriminability and Response Bias on Rey Auditory Verbal Learning Test Delayed Recognition in Behavioral Variant Frontotemporal Dementia and Alzheimer’s Disease

Abstract: Objective: Episodic memory is impaired in Alzheimer’s disease (AD) dementia but thought to be relatively spared in behavioral variant frontotemporal dementia (bvFTD). This view is challenged by evidence of memory impairment in bvFTD. This study investigated differences in recognition memory performance between bvFTD and AD. Method: We performed a retrospective analysis on the recognition trial of the Rey Auditory Verbal Learning Test in patients with bvFTD (n = 85), AD (n = 55), and cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 51 publications
0
3
0
Order By: Relevance
“…Response bias is another index calculated in recognition. We found that the AD group exhibited significantly lower (more liberal) response bias than the MCI and HC groups which was consistent with previous studies [ 21 , 22 ]. However, the results of MCI remain unclear.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Response bias is another index calculated in recognition. We found that the AD group exhibited significantly lower (more liberal) response bias than the MCI and HC groups which was consistent with previous studies [ 21 , 22 ]. However, the results of MCI remain unclear.…”
Section: Discussionsupporting
confidence: 93%
“…Previous research has indicated that the process approach played an important role in diagnosing and tracking the progression of cognitive impairment. Most researchers found that AD subjects had impaired discriminability and more liberal response bias [ 21 , 22 ]. Discriminability was helpful in predicting conversion from MCI to AD, and adding discriminability to the delay recall created a better predictive tool [ 23 , 24 ].…”
Section: Introductionmentioning
confidence: 99%
“…In another poster, Cecchini et al (2017c) showed that the free recall version of the STM binding test could differentiate AD from amnestic bvFTD. That is important because AD and amnestic bvFTD showed the same pattern of episodic memory deficits on the RAVLT test, thus the free recall binding task could be used to differentiate AD from bvFTD even when the latter show episodic memory deficits, which is not unusual (Hornberger et al, 2010; van den Berg et al, 2020). Therefore, free recall and change detection tasks could assess binding through different brain networks.…”
Section: Discussionmentioning
confidence: 99%
“…Regarding RP and IW, instead, the AD group performed similarly to the other groups, except for DEP and SCD. Visual recognition deficit has been reported in a part of AD and MCI patients [26], but it can be observed, even if to a lesser extent, also in other dementia, such as bvFTD [27] and DLB [28]. The possible reasons why we did not find significant differences in RP between groups are the slight impairment of RP in the other dementia groups as well, along with the very mild global cognitive impairment (average MMSE = 25.8) of The AUC value and the cut-off scores (lower part of the cell) of the index used to compare group pairs with 95% confidence level (CL) computed with a bootstrap method, are showed.…”
Section: Discussionmentioning
confidence: 99%